Baited: A Tropical Fish Yearns for Snow and the Anglophone Reception of Japanese Yuri Romance Manga - Joseph Crawford (Journal of Popular Romance Studies, 2025)
This article investigates the Anglophone reception history of the Japanese yuri romance manga genre, which depicts relationships between girls or young women. By surveying a representative corpus of Japanese yuri manga that has been translated and published in English, it describes the conventions and tropes of the genre, as well as their relationship to traditional Japanese models of same-sex intimacy between women. It then discusses the tensions between these conventions and the expectations of the genre's Anglophone readers, as expressed through comments and discussions in online spaces devoted to Western yuri fandom. Finally, the Western reception history of the manga series A Tropical Fish Yearns for Snow is used as a case study for exploring the frustrations of Anglophone audiences with yuri conventions and their significance for the cross-cultural reception of queer romance media.